Carbon emission effect of urbanization at regional level: Empirical evidence from China - Honglei Niu; William Lekse (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
Historically, global urbanization has been an essential ingredient for national economic growth and beneficial social transformation. However, with the global urban population currently generating two-thirds of all carbon emissions, global policymakers are urging mayors and regional leaders to make difficult decisions to reduce the negative impacts of urbanization on the environment. The authors begin their examination of the implications of local and regional factors by applying the Dynamic Spatial Durbin Panel Data Model to empirically examine aspects of developing low-carbon strategies for the rapidly expanding size and number of the world's urban areas. The results indicate that the contribution of urbanization to carbon emissions can be positively affected when regional policy makers collaborate to focus on spillover effects to simultaneously manage the scope, diversity, and complexity of economic and environmental issues from the perspective of creating a balance between rapid urbanization and relevant regional factors. Regional leaders can make a difference by creating both short-term goals and long-term strategies for maintaining low-carbon urbanization, nurturing regional coordination, monitoring and managing eco-friendly regional spillover effects, supporting low-carbon technology innovations, and maintaining optimal city size.
Keywords: Q51; R11; 330; carbon emission effect; urbanization; local and regional focus; STIRPAT; Dynamic Spatial Durbin Panel Data Model